2型糖尿病患者の睡眠状態の生理学的検討 - 近藤 ふさえ (JOURNAL OF THE KYORIN MEDICAL SOCIETY, 2006)
Among lifestyle-related diseases, diabetes is closely associated with sleep disorders such as difficulty falling asleep, arousal during sleep, and early morning awakening. In the present study, the level of activity during non-active periods (sleep period) was analyzed in patients with type 2 diabetes mellitus (T2DM) using a portable physical activity measuring device (Actigraph), in order to elucidate the characteristics of the sleep condition of these patients. Subjects were 18patients with T2DM (11 men, 7 women) aged 35 to 65 years (mean age, 50.2±10.2 years), with a mean HbA1c level of 10.6±3.2%. In addition, the relationship between level of activity and subjective sleepiness was analyzed using the OSA sleep inventory (MA version). Furthermore, subjective sleepiness for the month preceding admission was assessed using the Pittsburgh Sleep Quality Index (PSQI), and its relationship to HbA1c was analyzed.The results showed that HbA1c tended to increase proportionally with PSQI-Global score. Comparison of proportion of level of activity (mG)=0 during non-active periods between T2DM patients, adults, and elderly revealed that T2DM patients had the lowest proportion, with a significant difference relative to adults (ANOVA, p<0.017, df=25, F=4.912). T2DM patients were classified into the following groups based on their characteristics during non-active periods: I) patients with a favorable sleeping pattern, II) patients with a high level of activity during non-active periods and good subjective sleepiness, and III) patients with a high level of activity and poor subjective sleepiness. Factors contributing to poor subjective sleepiness in T2DM were sleep disorders such as difficulty falling asleep and the incidence of waking after sleep onset, which occurred with increases in the level of activity when falling asleep and during sleep, respectively. These findings suggest that patients with T2DM may suffer from sleep disorders before they become aware of their inability to fall asleep. 生活習慣病の中でも糖尿病患者は入眠困難，中途覚醒，早朝覚醒などの睡眠障害をきたしやすい状態にあるといわれている。本研究は，糖尿病患者の睡眠状態の特徴を明らかにするために，2型糖尿病患者18名（男性11名，女性7名）で35歳から65歳，年齢50.2±10.2歳を対象に携帯型身体活動測定器（Actigraph）を用いて非活動期（睡眠期）の行動量を分析した。また，行動量と主観的睡眠感の関連を明らかにするためにOSA睡眠調査票MA版を用いた。さらにHbA1cとの関連は，1ヶ月間の主観的睡眠感を反映するPittsburgh睡眠質問票（PSQI）を用いて調査し分析を行った。その結果，2型糖尿病患者と健康成人，介護福祉施設入所高齢者との非活動期（睡眠期）における活動量（mG=0）の比率の比較では，有意な差が認められた（ANOVA, p=0.017 df=25 F=4.912）。2型糖尿病患者の非活動期（睡眠期）の特徴を分類すると，i）睡眠覚醒良好群，ii）非活動期（睡眠期）に行動量多いが主観的睡眠感良好群，iii）非活動期（睡眠期）に活動量が多く主観的睡眠感不良群に分類できた。また，PSQI-Global scoreの得点が高くなるほどHbA1cが高くなる傾向がみられた。2型糖尿病患者の主観的な良い睡眠を阻害する要因は，入眠時と中途における活動量の増加に伴う入眠困難と中途覚醒よる睡眠障害であった。2型糖尿病患者は「眠れない」と自覚する以前から睡眠障害が潜在している可能性が示唆された。